Metabolite profiling of bark and secondary branches of Holarrhena pubescens Wall.ex G.Don by chromatographic and tandem mass spectroscopic analyses - Cheruthazhakkat, Sulaiman; Palamadathil Kozhicheri, Mufeeda; Erayur Mana, Anandan; Balachandran, Indira (Vegetos - International journal of plant research, 2025)
Holarrhena pubescens is an important medicinal plant used in Ayurveda and other traditional systems of medicine. Bark of this tree is used in Ayurveda to treat dysentery, especially amoebic dysentery. This study is aimed at exploring the possibilities of using secondary branches of H. pubescens as a sustainable alternative to its bark, which is subject to overexploitation due to its high medicinal demands. Comparative chemical evaluation has been carried out in the bark and secondary branches of this species using various spectrophotometric and high-performance thin-layer chromatographic studies. Detailed metabolite profiling was done by  liquid chromatography mass spectroscopic evaluation. The result showed that the chemical constituents of both bark and secondary branches are almost similar; however, the abundance of individual compounds showed differences. Concentrations of phenolics and flavonoids are found to be higher for bark than its secondary branches. Minor variations of chemical constituents were also observed among the different collections. LC/MS analysis showed that major metabolites are common for both bark and branches, which provided a lead for further studies to ensure the therapeutic potential.